Analgesic Effects Evoked by Real and Imagined Acupuncture: A Neuroimaging Study. (23rd August 2018) - Cao, Jin; Tu, Yiheng; Orr, Scott P; Lang, Courtney; Park, Joel; Vangel, Mark; Chen, Lucy; Gollub, Randy; Kong, Jian
Abstract: Acupuncture can provide therapeutic analgesic benefits but is limited by its cost and scheduling difficulties. Guided imagery is a commonly used method for treating many disorders, such as chronic pain. The present study examined a novel intervention for pain relief that integrates acupuncture with imagery called video-guided acupuncture imagery treatment (VGAIT). A total of 27 healthy subjects were recruited for a crossover-design study that included 5 sessions administered in a randomized order (i.e., baseline and 4 different interventions). We investigated changes in pain threshold and fMRI signals modulated by: 1) VGAIT, watching a video of acupuncture previously administered on the participant's own body at baseline while imagining it being concurrently applied; 2) a VGAIT control condition, watching a video of a cotton swab touching the skin; 3) real acupuncture; and 4) sham acupuncture. Results demonstrated that real acupuncture and VGAIT significantly increased pain threshold compared with respective control groups. Imaging showed that real acupuncture produced greater activation of the insula compared with VGAIT. VGAIT produced greater deactivation at the rostral anterior cingulate cortex. Our findings demonstrate that VGAIT holds potential clinical value for pain management.